Edukasi Penggunaan Obat Saat Bulan Puasa Di Tinjau Secara Syariah Pada Pasien Skizoprenia Di Soerojo Hospital Magelang - Sabiti, Farroh Bintang; Febriliani, Sari; Magfirah, Noor Wildiati (Sultan Agung Islamic University of Semarang, 2022)
Background: Schizophrenia is a chronic disorder that often relapses or is characterized by delusions, hallucinations, confusion, and strange thoughts, abnormal motor behavior and negative symptoms. In overcoming mental disorders, the role of religion is important based on the verses of the Qur'an and the Sunnah of the Prophet. So that treatment may not only be cured by taking medicine but also by getting closer to the healer. The purpose of this study was to determine the effect of education on how to take medicine according to sharia in schizophrenic patients in hospitals in Magelang. Methods: This research is a type of qualitative descriptive research. Data collection in this study was carried out in February-March 2022. This study used a questionnaire as a data collection instrument and information delivery media using leaflets. Result & Conclusion: Characteristics of schizophrenic patients are mostly male (60%) with an age range of 15-18 years (73%) and there is an influence of understanding between before and after being given education about taking medication according to sharia in schizophrenia patients.